Strategy for Optimizing the Potential of Local Resources Through Mapping the Potential of Mertelu Village & Hargomulyo Village and Hargomulyo Village, Gedangsari District, Gunungkidul DI Yogyakarta - Muhammad Iqbal; Faizal Makhrus (Help: Journal of Community Service, 2024)
The community service program conducted in Gedangsari District, Gunungkidul, Yogyakarta, aimed to optimize the potential of local resources in Mertelu and Hargomulyo Villages through comprehensive territorial mapping. The initiative was driven by the need to enhance the economic development of rural areas with abundant but underutilized natural resources. The methodology involved participatory mapping, GIS analysis, structured interviews, and direct observations to document the distribution of natural resources, MSMEs, and infrastructure. The results revealed significant opportunities for developing eco-tourism and agricultural industries, particularly in areas with underutilized land. Additionally, the program successfully increased community capacity by providing training in mapping technologies, leading to greater local involvement in planning processes. The conclusion underscores the effectiveness of territorial mapping as a tool for rural development, highlighting the potential for this approach to be replicated in other regions facing similar challenges. Future community empowerment efforts should focus on sustainable practices and continued capacity-building to ensure long-term economic and social benefits for the local population.